A review of the species of Euroleon (Neuroptera: Myrmeleontidae) from China - Bao, Rong; Wang, Xinl L. (Zootaxa, 2006)
The species of Euroleon (Neuroptera: Myrmeleontidae) from China are reviewed. Euroleon parvus Hölzel, 1972 and E. polyspilus (Gerstaecker, 1885) are newly recorded in China. Euroleon sanxianus is proposed as a new synonym of Euroleon coreanus. A key to the examined species of Euroleon from China is given and geographic distributions are discussed.